تعرف على الجنوب التونسي: شط الجريد والواحات - بن وزدو, الهادي (Simpact, 1999)
Keywords: Géographie – Chott el-Jarid

Le lac Tritonis et les noms anciens du chott el Jérid - Peyras, Jean; Trousset, Pol (Antiquités africaines, 1988)
Long before being a matter of debate for the modern scholars about the famous project of the Saharian Sea, the lake Tritonis (or Tritônitis) had been a problem for ancient geographers themselves as to its localisation along the Libyan coastal areas. Linked or not with the legend of Argonauts and with the myth of a native goddess assimilated to Pallas, bay or lake, the Triton seems to belong to a mythical geography more than to reality. Several localisations were given as possible according to different traditions of Greek geographers and the question had remained unsettled up to the Roman period. For Strabo following a first tradition, the hydronym was settled in Cyrenaica prior to be wrongly translated on the Atlantic shoreline with the garden of Hesperids. On the other hand, for a long tradition illustrated by Herodotus, the Tritonis could be placed — as Gsell emphasized — nowhere but in the gulf of Gabes itself. However, contradictory data in the « Pseudo-Scylax » are leading either to Byzacium or to Lesser Syrtis ; in Pliny influenced by two different traditions, the Tritonis is elusively quoted as « inter duas Syrtis ». Mela was the only one (with perhaps Ptolemaeus) to give to palus and inland position which can be identified clearly with the Great Chott — already without any connexion with the sea — in southern Tunisia.
Keywords: Géographie – Chott el-Jarid